Environmental regulation of virulence in group A streptococci: transcription of the gene encoding M protein is stimulated by carbon dioxide. - Caparon, M G (1992)
We have found that different atmospheres can have significant effects on the transcription of emm, the gene that encodes M protein, the major virulence factor of the group A streptococcus (Streptococcus pyogenes). Expression of emm was monitored by constructing a transcriptional fusion of the promoter for emm6.1 from S. pyogenes JRS4 to a promoterless chloramphenicol acetyltransferase gene. Transcription, as measured by determining chloramphenicol acetyltransferase specific activity, was stimulated by as much as 25-fold by increased carbon dioxide tension. Expression was greater in the latter stages of growth and was not affected by growth at 30 instead of 37 degrees C. Insertional inactivation of mry, a gene encoding a positive regulator of emm6.1, reduced chloramphenicol acetyltransferase activity below the detectable level. We conclude that expression of emm is influenced by environmental factors and that the level of carbon dioxide is one signal that may influence expression of M protein during infection.